Differential improvement in transpiration efficiency of C3 and C4 crop plants under elevated CO2 conditions - LAKSHMI, N JYOTHI; VANAJA, M; YADAV, S K; MAHESWARI, M; PATIL, AMOL; PRASAD, CH RAM; SATISH, P; VENKATESWARLU, B (The Indian Journal of Agricultural Sciences, 2014)
Sunflower plants (C3) transpired more water than pearl millet (C4) from seedling to maturity under ambient conditions. The transpiration (water use) at elevated CO2 was lesser for pearl millet and higher for sunflower compared to ambient. Elevated atmospheric CO2 increased TE more in pearl millet (21.9%) than in sunflower (10.5%) and decreased the TR or water transpired to produce dry mass by 18.1% in pearl millet and 9.7% in sunflower compared to ambient. As the CO2 content of the air continues to rise, both sunflower (C3) and pearl millet (C4) agriculture crops will respond favorably by exhibiting increases in TE.